Komite Audit Dan Profitabilitas Mempengaruhi Audit Delay Pada Perusahaan Publik Sektor Energi Tahun 2020-2022 - Christian Vanda Situmeang; Jhon Rinendy; Judith Tagal Gallena Sinaga (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study plans to assess the impact of review councils and productivity on postpones in sending yearly monetary reports that have been evaluated by open bookkeeping firms in energy area organizations recorded on the Indonesia Stock Trade (IDX) from 2020 to 2022. Utilization of auxiliary information from 258 populace monetary reports gave by 86 public organizations was completed, yet just 63 evaluated monetary reports met the rules for being inspected utilizing the purposive examining technique. The exploration results show that the review panel and company productivity all the while adversely affect review delays. In any case, to some degree, the quantity of review council individuals doesn't show a huge effect on review delays, with the exception of the degree of organization productivity. Keywords: audit delay, audit committee, profitability